SUDDEN SUSPICIOUS LOOKING UNEXPECTED NATURAL CARDIAC DEATHS: A CASE SERIES STUDY AND IN-DEPTH REVIEW - Sharma, Surendra K; Kumar, Rajesh; Singh, Jitender Pratap; Verma, Sunita; Arathi (Journal of Forensic Medicine and Toxicology, 2020)
Sudden cardiac death (SCD) is a major cause of mortality secondary to coronary artery disease (CAD). Though it is one of the commonest causes of natural death but is contested too often. SCD of someone under the suspicion of violence means differently to different persons. Larger perception of the death due to suspected or known violence ignites an intolerance debate “Pro SCD versus Anti SCD”. Controversy into the cause of death ultimately ends but acrimony lingers.
Keywords: practitioners; cardiac death (SCD)